Changing the Care Paradigm for Patients: Advanced Illness Beds Care Model. (November 2021) - Rimar, Alexander; Friedman, M. Isabel; Quinteros, Maria G.; Gooch, Rebecca A.; Masick, Kevin D.; DaCosta, Nicholas; Spooner, Rachael L.
Background: Over 90 million Americans suffer from advanced illness (AI) and spend their last days of life in critical care units receiving costly, unwanted, aggressive medical care. Objective: Evaluate the impact of a specialized care model in medical/surgical units for hospitalized geriatric patients and patients with complex care requirements where designated AI beds align care with patient's wishes/goals, minimize aggressive interventions, and influence efficient resource utilization. Design: US based multi-facility retrospective, longitudinal descriptive study of screened positive AI patients in AI Beds (N = 1, 237) from 3 facilities from 2015 to 2017. Results: Patient outcomes included 60% referrals to AI beds from ICU, a decrease of 39-49% in average ICU LOS, a 23% reduction of AI bed patient expirations, 9.0% referrals to hospice, and projected cost savings of 4, 361.66/patient, US dollars. Conclusion: Allocating AI beds to deliver care to AI patients resulted in a decreased cost of care by reducing overall hospital LOS, mortality, and efficient use of both critical care and hospital resources.